The Act on Securing the Socialist Discipline of Labour - Chumiński, Jędrzej (Studia Historiae Oeconomicae, 2012)
Labour belonged to the most important values in the catalogue declared by the ideologists of communism. Paradoxically and contrary to the propaganda, the quality of labour was one of the major weaknesses of the communist system in Poland since its beginning and a source of its demise in the long run. A measure of its irrationality could be the fact that throughout its existence it was impossible to create a mechanism promoting good labour, whereas the remedies undertaken often did not improve the situation, but even made it deteriorate. In some periods they even reflected the totalitarian character of the state. The article presents the premises governing low labour productivity in nationalized workplaces during the first decade of the so called People’s Poland, as well as the activities undertaken by the regime to improve labour discipline during the Stalinist times. In this context, the article discusses the impact of the Act on Securing the Socialist Discipline of Labour passed in January 19, 1950. It was in fact a special act – its consequence was having more than 800 thousand cases referred to court, about 350 thousand people convicted, while more than 30 thousand sent to prison.